2015
DOI: 10.1002/wnan.1374
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress by inorganic nanoparticles

Abstract: Metallic and metallic oxide nanoparticles (NPs) have been increasingly used for various bio-applications owing to their unique physiochemical properties in terms of conductivity, optical sensitivity, and reactivity. With the extensive usage of NPs, increased human exposure may cause oxidative stress and lead to undesirable health consequences. To date, various endogenous and exogenous sources of oxidants contributing to oxidative stress have been widely reported. Oxidative stress is generally defined as an imb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(68 citation statements)
references
References 178 publications
(320 reference statements)
2
66
0
Order By: Relevance
“…Besides cytotoxicity, previous study also found that silica coating significantly reduce DNA damage induced by ZnO nanorods [51]. Comparison between ZnO NPs and SiO 2 NPs also found that ZnO NPs are more toxic [52, 53, 54, 55]. …”
Section: Resultsmentioning
confidence: 98%
“…Besides cytotoxicity, previous study also found that silica coating significantly reduce DNA damage induced by ZnO nanorods [51]. Comparison between ZnO NPs and SiO 2 NPs also found that ZnO NPs are more toxic [52, 53, 54, 55]. …”
Section: Resultsmentioning
confidence: 98%
“…The protein function is specific to one conformation and an alteration can cause important cell injuries [114]. Both AgNPs and Ag + ions have been shown to interact with proteins, thereby leading to altered conformation, deactivation and even degradation [112,[115][116][117]. When AgNPs bind to proteins, they form corona structures and can express genes involved in DNA damage [112].…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, the higher level of TUNEL staining in the ZnO NP-treated group implied that keratinocyte apoptosis was increased and that the histological foundation for epidermal renewal capacity was impaired. Oxidative stress is generally thought to play a pivotal role in the mechanism by which nanomaterials damage cells [31]. The higher level of 8-OHdG staining in the ZnO NP-treated group revealed that ZnO NPs promoted DNA damage related to oxidative stress in pathological keratinocytes.…”
Section: Discussionmentioning
confidence: 87%
“…GSH prevents proteins from being damaged by ROS by oxidizing their own thiol groups [32]. The MDA level indicates the extent of lipid peroxidation [31]. The disturbance of GSH antioxidant system and the increased MDA level in the ZnO NP-treated group revealed the potential mechanism by which ZnO NPs promote in ammation and keratinocyte apoptosis in pathological skin.…”
Section: Discussionmentioning
confidence: 99%